Identification of Some Charcoal-Black-Pigmented CDC Fermentative Coryneform Group 4 Isolates as Rothia dentocariosa and Some as Corynebacterium aurimucosum: Proposal of Rothia dentocariosa emend. Georg and Brown 1967, Corynebacterium aurimucosum emend. Yassin et al. 2002, and Corynebacterium nigricans Shukla et al. 2003 pro synon. Corynebacterium aurimucosum - Daneshvar, Maryam I. (American Society for Microbiology, 2004)
Sixty-three clinical isolates of charcoal-black-pigmented, gram-positive coryneform rods were received for identification by the Centers for Disease Control and Prevention (CDC) and were provisionally designated CDC fermentative coryneform group 4 (FCG4). Forty-five of these were characterized by morphological, physiologic, antimicrobial susceptibility, cellular fatty acids, 16S rRNA gene sequencing, and DNA-DNA hybridization analyses. Nitrate reduction, cellular fatty acid analysis, 16S rRNA gene sequencing, and DNA-DNA hybridization studies segregated these strains into two groups: FCG4a (8 strains) and FCG4b (37 strains). The FCG4a strains, only one of which was from a female genitourinary source, produced cellular fatty acid and biochemical profiles similar to those observed with reference strains of Rothia dentocariosa and Rothia mucilaginosa, while the FCG4b strains were similar to Corynebacterium species. DNA-DNA hybridization analysis demonstrated species-level relatedness among six FCG4a tested strains and showed that they were a charcoal-black-pigmented variant of R. dentocariosa. Sixteen isolates of the FCG4b group, mainly from female genitourinary tract specimens, as well as the type strains of two recently named species, Corynebacterium aurimucosum and Corynebacterium nigricans, were shown by DNA-DNA hybridization analysis and the sequencing of the 16S rRNA gene to be related at the species level and unrelated to the type strain of R. dentocariosa; therefore, the Corynebacterium-like strains were classified as a charcoal-black-pigmented variant of C. aurimucosum, because this name has nomenclatural priority over C. nigricans. These findings indicate that FCG4 represents a heterogeneous group that contains pigmented variants of both R. dentocariosa and C. aurimucosum; hence, the descriptions of both R. dentocariosa and C. aurimucosum have been amended to include charcoal-black-pigmented variants, and C. nigricans is a pro synonym of C. aurimucosum.